Single-cell analysis of matrisome-related genes in breast invasive carcinoma: new avenues for molecular subtyping and risk estimation - Su, Lingzi; Wang, Zhe; Cai, Mengcheng; Wang, Qin; Wang, Man; Yang, Wenxiao; Gong, Yabin; Fang, Fanfu; Xu, Ling (Frontiers in Immunology, 2024)
The incidence of breast cancer remains high and severely affects human health. However, given the heterogeneity of tumor cells, identifying additional characteristics of breast cancer cells is essential for accurate treatment.Purpose: This study aimed to analyze the relevant characteristics of stromal genes matrix genes in breast cancer through the multigroup data of a breast cancer multi-database.The related characteristics of stromal genes matrix genes in breast cancer were analyzed using multigroup data from the breast cancer multi database in the Cancer Genome Atlas, and the differential genes of breast cancer matrix genes were identified using the elastic net penalty logic regression method. The risk characteristics of stromal genes matrix genes in breast cancer were determined, and matrix gene expression in different breast cancer cells was evaluated using real-time fluorescent quantitative polymerase chain reaction (PCR). A consensus clustering algorithm was used to identify the biological characteristics of the population based on the matrix molecular subtypes in breast cancer , followed by gene mutation, immune correlation, pathway, and ligand-receptor analyses.Results: This investigation revealed the distinct features of cellular matrix genes associated with breast cancer. Furthermore, a predictive risk model that leverages differential gene expression was formulated to predict the clinical outcomes in patients with breast cancer. PCR was used to quantify variations in the expression levels of matrix genes among distinct breast cancer cell types. Molecular subtypes were divided into five clusters, each exhibiting differences in gene mutation, drug-ready gene analysis, immune infiltration, and pathway analysis of different molecular subtypes. This study reveals the genetic characteristics of cell matrix related to breast cancer. It is found that 18.1% of stromal genes are related to the prognosis of breast cancer, and these genes are mostly concentrated in the biological processes related to metabolism and cytokines in protein. Five different matrix-related molecular subtypes were identified by using the algorithm, and it was found that the five molecular subtypes were obviously different in prognosis, immune infiltration, gene mutation and drug-making gene analysis.Conclusions: This study involved analyzing the characteristics of cell-matrix genes in breast cancer, guiding the precise prevention and treatment of the disease.